Motip-motip ekspansi Nederland dalam abad keenambelas - Luhulima, C. P. F., 1930- (Lembaga Research Kebudajaan Nasional. Terbitan tak berkala, 1971)
History of the Dutch expansion to Indonesia in the 16th century.